Studi Pengembangan Pasar Tradisional Pajak Ikan Sebagai Pusat Wisata Belanja Di Kota Medan - Dalimunthe, Femmy Indriany (JURNAL DESTINASI PARIWISATA, 2019)
This study aims to describe a picture of how potential is and what the appropriate development strategy for a traditional market in Medan, Pajak Ikan. This research was conducted by using descriptive method. The data was collected by interview and observation. Interviews were conducted with a few selected outlets randomly(random sampling). And observations conducted with the involvement of information from many parties involved, include society community and local government. Implementation of these research activities carried out for 10 months, starting from the preparation of proposals that have been field since December 2018 to September 2019. The results showed that Pajak Ikan in Medan has the potential to be developed into a shopping center in the city of Medan. Then for alternative development strategies that best fit based on the results of the analysis is a strategy QSPM SO1 (Strength-Opportunity) is a strategy that uses the internal strangth to take advantage of external opportunities that exist in the way of executing many events with grand publications in the area of Pajak Ikan. Keywords : potential shopping center, matrix TOWS, strategy